REDESAIN KAWASAN MASJID AMIR SAUD BIN FAHD KAMPUS II UNIVERSITAS ISLAM NEGERI ALAUDDINSAMATA GOWA - Marwati, Marwati; Zulkarnaen, Zulkarnaen (Nature : National Academic Journal of Architecture, 2015)
Alauddin State Islamic University or UIN Alauddin State Islamic University is located in the university Makassar.Sebagai berinisialkan Islam, of course, this university has facilities such as a facility to worship the mosque. Amir Saud Bin Fahd Mosque Campus II Alauddin State Islamic Uinversitas is also commonly used as a place to socialize among students there. However, the area of the mosque at the State Islamic University Alauddin less well ordered. Landscaping areas such as mosques, parking lots that are not clearly make that parked vehicles do not fit in place, access to the mosque that is not directed to make the students or Juma'ah not know the direction toward the mosque, which is less street furniture such as street lights, trash and furniture, as well as other landscape elements that can support student activities. To that end, the need to redesign the region Amir Saud Bin Fahd Mosque Campus II Samata Alauddin State Islamic University Gowa as the infrastructure is not only used as a place of worship, but also can serve as a place to socialize as well as ordering a science for students.